Produção de textos na escola: uma proposta didática com autobiografias no ensino fundamental II - Carla do Carmo Pinto (2021)
The research proposed here is focused on the teacher's practice, with the aim of proposing reflections that aim to encourage the production of texts at school, seeking to simultaneously achieve the interest and learning of students. Thus, its main objective is to produce a teaching project for teachers who want to work on the production of autobiographical texts in the 6th year of elementary school II. As a reference, I am based mainly on the conception of language as social interaction coming from the studies of Bakhtin (2011), some assumptions for the production of texts presented by Geraldi (1997 and 2012), regarding reading, I am guided by the basic sequence of literary literacy in Cosson (2006) and, on the concept of autobiography, I consider the studies by Bakhtin (2011) and Lejeune (2008). The choice of the autobiographical genre was based on the observation that students already produce different texts on social networks and that many are autobiographical texts. After studying the theoretical framework and the dissertations defended in the Program on the subject and based on my experience with teaching, I organized activities to build the Teaching Project. In the first stage, students are asked to observe that many texts produced on social networks are autobiographical, in the second stage they come into contact with autobiographical texts through reading, understanding and studying the structural characteristics of the genre. Then, in the third stage, activities are applied that induce students to reflect on their life trajectory, and thus acquire the necessary content for their autobiographical production in the next dynamic. The last step refers to the autobiographical production of each student and the work to improve their writing, leading to the publication of the books. It is expected that at the end of the activities, the student will feel motivated to produce texts and that they will present a significant improvement in their learning, developing an awareness of themselves and their own speech.